Presence and agency in real and virtual spaces: The promise of extended reality for language learning - Godwin-Jones, Robert (Language learning & technology, 2023)
Augmented and virtual realities (together “extended reality”) offer language learners the opportunity to communicate and interact in real and virtual spaces. In augmented reality (AR), users view computer-generated layers added to a phone camera’s view of the world. Virtual reality (VR) immerses users in a 3D environment that might simulate aspects of the outside world or project an entirely imagined reality. This column looks at opportunities and challenges in the use of extended reality (XR) for second language learning. Opportunities include higher learner motivation and personal agency through XR uses that feature collaboration and open-ended interactions, particularly in simulations, games, and learner co-design. That direction offers more alignment with current theories of second language acquisition (SLA)–emphasizing holistic language development and ecological frameworks–than most commercial VR apps currently available. Those posit a linear language development and focus largely on vocabulary learning and language practice within closed role-play scenarios. Offering both AR and VR access, mixed reality may present opportunities to combine the best features of each medium. Advances in generative artificial intelligence (AI) provide additional possibilities for personalized language learning in a flexible and dynamic VR environment.